Protease-activated receptor 4 activity promotes platelet granule release and platelet-leukocyte interactions. (2nd January 2019) - Rigg, Rachel A.; Healy, Laura D.; Chu, Tiffany T.; Ngo, Anh T. P.; Mitrugno, Annachiara; Zilberman-Rudenko, Jevgenia; Aslan, Joseph E.; Hinds, Monica T.; Vecchiarelli, Lisa Dirling; Morgan, Terry K.; Gruber, András; Temple, Kayla J.; et al.
Abstract: Human platelets express two protease-activated receptors (PARs), PAR1 (F2R) and PAR4 (F2RL3), which are activated by a number of serine proteases that are generated during pathological events and cause platelet activation. Recent interest has focused on PAR4 as a therapeutic target, given PAR4 seems to promote experimental thrombosis and procoagulant microparticle formation, without a broadly apparent role in hemostasis. However, it is not yet known whether PAR4 activity plays a role in platelet-leukocyte interactions, which are thought to contribute to both thrombosis and acute or chronic thrombo-inflammatory processes. We sought to determine whether PAR4 activity contributes to granule secretion from activated platelets and platelet-leukocyte interactions. We performed in vitro and ex vivo studies of platelet granule release and platelet-leukocyte interactions in the presence of PAR4 agonists including PAR4 activating peptide, thrombin, cathepsin G, and plasmin in combination with small-molecule PAR4 antagonists. Activation of human platelets with thrombin, cathepsin G, or plasmin potentiated platelet dense granule secretion that was specifically impaired by PAR4 inhibitors. Platelet-leukocyte interactions and platelet P-selectin exposure the following stimulation with PAR4 agonists were also impaired by activated PAR4 inhibition in either a purified system or in whole blood. These results indicate PAR4-specific promotion of platelet granule release and platelet-leukocyte aggregate formation and suggest that pharmacological control of PAR4 activity could potentially attenuate platelet granule release or platelet-leukocyte interaction-mediated pathological processes.